Strategi Pembelajaran Tahfidzul Qur'an dan Implikasinya terhadap Pemahaman Studi Keislaman - Luthfi, Moh; Subando, Joko (TSAQOFAH, 2025)
This article discusses various tahfidzul Qur’an learning strategies and their relationship to enhancing comprehensive understanding of Islamic studies. Tahfidz learning not only emphasizes the cognitive aspect of memorization but also involves the affective and spiritual dimensions of the learners. The study aims to identify effective instructional strategies for improving both the quality of Qur’anic memorization and mastery of Islamic subjects. The strategies examined include expository, inquiry-based, problem-based, cooperative, contextual, and affective approaches, grounded in behaviorist theory as the conceptual framework. Methods such as wahdah, jibril, yanbu’a, muroja’ah, and tilawati are also analyzed as effective techniques in Qur’an memorization. The findings indicate that the use of well-planned and integrated strategies positively impacts both memorization quality and comprehension of Islamic studies, including aqidah, fiqh, tasawuf, tafsir, hadith, and modern as well as interdisciplinary methodological approaches. Thus, optimal tahfidzul Qur’an instruction can significantly strengthen the intellectual and spiritual dimensions of learners in the context of contemporary Islamic education.